Using FRAPTRAN 1.5 code for safety evaluation of TVS-2006 fuel rod under transient conditions of VVER-1200 (AES-2006) reactor - Do , Ngoc Diep; Phung , Khac Toan (Nuclear Science and Technology, 2015)
This article shows the results of important thermal-mechanical parameters related to the TVS-2006 fuel rod design which were analyzed and evaluated by using FRAPTRAN1.5 code. Based on the data given in the Preliminary Safety Analysis Report (PSAR) of AES-2006 (Novovoronezh NPP-2 Power Unit No.1)and FRAP-T (Fuel Rod Analysis Program-Transient), FRAPTRAN1.5 calculations of TVS-2006 fuel rod behaviors in Loss of Coolant Accidents and Reactivity-Initiated Accidents conditions have been made. The calculated results related to safety criteria of fuel element and cladding temperatures, cladding stress and strain, fuel enthalpy, local oxide thickness, gap gas pressure, and elongation of fuel rod have been compared with the ones given in AES-2006 PSAR. A good agreement has been observed between AES-2006 PSAR andFRAPTRAN1.5 calculations.